Relationship of domestic violence from husband and preeclampsia in postpartum women referred to Sanandaj medical education center in 2017 - Serve Mohamadi; Roonak Shahoei; Nasrin Soofizadeh (Mashhad University of Medical Sciences, 2021)
Introduction: Preeclampsia is one of the pregnancy complications and is a multiple organ disorder that occurs in 3 to 5 percent of all pregnancies in western countries. Regarding to the involvement of the autonomic and sympathetic systems in pathophysiology of preeclampsia, the role of stress is highlighted in exacerbating the condition. Since the role of factors such as domestic violence is raised in the incidence or exacerbation of preeclampsia, and with regard to the growth and prevalence of domestic violence in the country, this study was performed with aim to determine the association between domestic violence and preeclampsia. Methods: This case-control study was performed on110 post-partum women in two groups of 55 subjects (preeclampsia and non-preeclampsia) in Beasat hospital of Sanandaj in 2017. Demographic data were collected using researcher-made Demographic-Midwifery questionnaire, and then data related to domestic violence using World Health Organization domestic violence questionnaire. Data were analyzed using SPSS software (version 22) and t-test, Mann-Whitney and Chi-square tests. P <0.05 was considered statistically significant. Results: There was no significant relationship between domestic violence by husband and preeclampsia (P = 0.203). The risk of preeclampsia in the case of domestic violence and physical violence was 1.5 times than control group, sexual violence was 1.6 times than control group, and psychological violence was 1.2 times than control group. There was no significant association between physical, sexual and mental violence with preeclampsia (P=0.328, P=0.473 and P=0.606, respectively). Conclusion: No significant relationship was found between the incidence of preeclampsia and the types of violence.